2007
DOI: 10.1523/jneurosci.4101-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Kynurenine Pathway in Human Neurons

Abstract: The kynurenine pathway is a major route of L-tryptophan catabolism producing neuroactive metabolites implicated in neurodegeneration and immune tolerance. We characterized the kynurenine pathway in human neurons and the human SK-N-SH neuroblastoma cell line and found that the kynurenine pathway enzymes were variably expressed. Picolinic carboxylase was expressed only in primary and some adult neurons but not in SK-N-SH cells. Because of this difference, SK-N-SH cells were able to produce the excitotoxin quinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
287
3
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(302 citation statements)
references
References 62 publications
10
287
3
2
Order By: Relevance
“…In addition to suppressing antitumor immune responses and promoting cell survival and cell motility, trp metabolism may thus also constitute a novel metabolic mechanism to confer resistance of tumor cells to radiochemotherapy. This metabolic pathway may explain why NAD þ -depleting agents, such as FK866, are of limited efficacy in some tumors such as malignant gliomas and neuroblastomas, where quinolinic acid has been shown to be proproliferative (56,57). The resistance mechanism, as suggested by our data, seems to be regulated at the level of QPRT, which is why this enzyme may be a novel therapeutic target in malignant gliomas.…”
Section: Discussionmentioning
confidence: 71%
“…In addition to suppressing antitumor immune responses and promoting cell survival and cell motility, trp metabolism may thus also constitute a novel metabolic mechanism to confer resistance of tumor cells to radiochemotherapy. This metabolic pathway may explain why NAD þ -depleting agents, such as FK866, are of limited efficacy in some tumors such as malignant gliomas and neuroblastomas, where quinolinic acid has been shown to be proproliferative (56,57). The resistance mechanism, as suggested by our data, seems to be regulated at the level of QPRT, which is why this enzyme may be a novel therapeutic target in malignant gliomas.…”
Section: Discussionmentioning
confidence: 71%
“…Neurotoxicity would then negate these neuroprotective effects. The exact mechanism by which neuroprotection occurs is unclear, as PIC does not seem to interfere with the glutamate/NMDA binding site on the NMDA receptor (32). Thus, a highly regulated balance in the production of QUIN, PIC, and KYNA is required for normal neuronal function.…”
Section: Involvement Of the Kp In Neurotoxicitymentioning
confidence: 99%
“…Most cancer cells show a high rate of NAD þ turnover due to continuous and elevated PARP activation from DNA damage and genomic instability (73), and have significantly higher energy consumption compared with nontransformed cells (74). Interestingly, we have previously shown that ACMSD expression is absent and IDO-1 is overexpressed in the neuroblastoma cell line compared to human neurons, which express ACMSD (32). We also showed that QUIN was catabolized and PIC was produced in human neurons, whereas the neuroblastoma cell line showed a preference towards QUIN production and PIC consumption (32).…”
Section: Acmsd Dysregulation In Tumor Cells: a Speculative Role For Bmentioning
confidence: 99%
“…SNPs within CCBL1 and CCBL2 moderated the relationship between ADHD total, inattentive, and hyperactive-impulsive symp- tom severity. CCBL1 and CCBL2 encode kynurenine aminotransferase I and II, respectively, which transaminate kynurenine into the neuroprotective kynurenic acid [Guillemin et al, 2007;Myint et al, 2007;Vecsei et al, 2013]. Kynurenic acid is an antagonist at the N-mehtyl D-aspartic acid (NMDA) and a7 nicotinic acetylochoine (a7nACH) receptors that are implicated in learning [Hilmas et al, 2001].…”
Section: Discussionmentioning
confidence: 99%